The Lower Cretaceous Glance Conglomerate and Morita Formation of the Sierra El Chanate, northwestern Sonora - César Jacques-Ayala (Revista Mexicana de Ciencias Geológicas)
The Lower Cretaceous Glance Conglomerate and Morita Formation are well exposed in the sierra El Chanate, about 20 km northeast of Caborca, northwestern Sonora, México… in order to continue, download the full paper in PDF.